EFFECT OF ADDITION DIFFERENT LEVELS OF SOYBEAN OIL IN COMMERCIAL FISH FEED ON GROWTH PERFORMANCE, FEED EFFICIENCY, EPA AND DHA FOR PERKASA PANGASIID (Pangasianodon hypophthalmus Sauvage, 1878) - Arifah, Fajar Nurul; Rostika, Rita; Herawati, Titin; Pratiwy, Fittrie Meyllianawaty; Darmawan, Jadmiko (AQUASAINS, 2023)
Pangasius is a freshwater fish included in the main commodity by the Ministry of Marine Affairs and Fisheries, Indonesia. Siamese catfish production ranked 4th in freshwater fish commodities in 2016 after goldfish, tilapia, and catfish. Pangasius has a lack of EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid) if compared with fish from the sea. Application of additional different levels of soybean oil in commercial fish fed to enhance EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid) in Perkasa pangasiid flesh. This study was conducted to determine the effect of adding soybean oil with different levels of commercial fish feed given to Perkasa striped catfish on growth performance, feed efficiency, EPA (Eicosapentaenoic acid), and DHA (Docosahexaenoic acid). This experimental study used a Complete Randomized Design (CDR) with triplicates and five treatments with additional levels of soybean oil in commercial fish fed: (a) 0%, (b) 2%, (c) 4%, (d) 6%, and (e) 8%. The result showed that treatment of (e) is the best treatment for increasing the EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid) in Pangasius flesh. However, additional different levels of soybean oil in the commercial fish feed have no negative effect on growth performance and feed efficiency in Perkasa pangasiid.